Interface Quality, Perceived Enjoyment, dan Perceived Trust terhadap Niat Pembelian Menggunakan Aplikasi E-commerce Lazada - Marhaeni, Trecya Diyah Citra; Hayu, Rina Suthia (Universitas Islam Kadiri, 2023)
In the era of globalization and ever-developing information technology, online shopping through e-commerce has become one of the main choices for consumers throughout the world. Lazada is an e-commerce platform in Indonesia which has become the main e-commerce for shopping and selling products online in the Southeast Asia region since 2012. This research aims to examine the influence of interface quality, perceived enjoyment, and perceived trust on purchase intentions using Lazada e-commerce application. The data used is primary data. This research is included in quantitative research with a purposive sampling technique. The population of this study were Lazada users and the research respondents used were 258 respondents. This research uses SEM-PLS version 4.0. The results of this research show that interface quality has a positive but not significant effect on purchase intention. Then perceived enjoyment and perceived trust have a significant positive effect on purchase intention.